2010
DOI: 10.1177/1049732310368405
|View full text |Cite
|
Sign up to set email alerts
|

The Stories of Young People Living With a Liver Transplant

Abstract: Adolescence is a difficult time for those with chronic illness because of the constraints of the illness on developmental tasks. Little is known about the impact liver transplantation has during adolescence. In this study we aimed to explore, in their own words, young people's lived experience of life after transplantation. We used semistructured interviews to collect narrative data, and used a purposive sample of 14 young people in early, middle, and late adolescence, transplanted for a range of chronic, acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
68
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 57 publications
(79 citation statements)
references
References 45 publications
7
68
0
4
Order By: Relevance
“…The participants did report finding meaning and positive benefits from facing their disease. These findings are similar to those of other studies of adolescents and young adults living with chronic illness who also reported a struggle to make meaning in the face of a life-threatening illness (Jessup & Parkinson, 2010;Taylor et al, 2010). According to Parry and Chesler (2005), reports of benefit finding and meaning making are signs of psychosocial thriving posttreatment; however, the isolation and lack of support reported by survivors could predispose this population to be at risk for psychological late effects.…”
Section: Discussionsupporting
confidence: 90%
“…The participants did report finding meaning and positive benefits from facing their disease. These findings are similar to those of other studies of adolescents and young adults living with chronic illness who also reported a struggle to make meaning in the face of a life-threatening illness (Jessup & Parkinson, 2010;Taylor et al, 2010). According to Parry and Chesler (2005), reports of benefit finding and meaning making are signs of psychosocial thriving posttreatment; however, the isolation and lack of support reported by survivors could predispose this population to be at risk for psychological late effects.…”
Section: Discussionsupporting
confidence: 90%
“…This is especially important as currently available outcome measures not necessarily reflect young people's lived experience of liver transplantation [37].…”
Section: Discussionmentioning
confidence: 99%
“…In a phenomenological study examining the lived experience of children 7 to 15 years of age, key themes related to pediatric LT comprised children feeling the same yet different relative to peers, considering extraordinary events such as hospitalization as ordinary and familiar, experiencing recurrent pain, parental concern and worry, and children globally viewing themselves as healthy yet normalcy being reported as, "a reality and illusion" [18]. Taylor et al found that most pediatric LT recipients desired normalcy and avoided distinguishing themselves as different from others [19]. In order to achieve this normalcy a perception of wellness appears to be maintained, at times to the detriment of treatment adherence and in the hope of not being viewed as abnormal or unwell.…”
Section: Discussionmentioning
confidence: 99%